The interplay of family dynamics and social factors on underweight in children under-five in Zambia; addressing a neglected trend - Herbert Tato Nyirenda; Yordanos Gebremeskel; James Mulenga; Teza Sinyangwe (Discover Social Science and Health)
Abstract Background Undernutrition is the most critical aspect of malnutrition and poses significant concerns in children under five. Despite its multifaceted nature, there remains limited documentation on the intricate interplay between family dynamics and social factors contributing to undernutrition. This paper explored the interplay of family dynamics and social factors on underweight in under-five children in Zambia. Methods The paper used data pooled from cross section units drawn from the 2007, 2013/14 and 2018 Zambia Demographic Health Survey (DHS) whose primary objective was to provide up-to-date estimates of basic demographic and health indicators. Chi-square (χ2) analysis and multilevel mixed-effects logistic regression was employed. Results The findings indicate a 4% decrease in underweight between 2007 and 2018. Female children (aOR = 0.83, 95% CI 0.716–0.958), those receiving secondary education (aOR = 0.76, 95% CI 0.589–0.989), families in rural areas (aOR = 0.75, 95% CI 0.590–0.944) and families in the middle (aOR = 0.65, 99% CI 0.526–0.814) and higher (aOR = 0.64, 99% CI 0.485–0.844) wealth brackets, had a reduced risk of having underweight children. Conversely, households experiencing domestic violence (aOR = 1.22, 95% CI 1.011–1.475) and those not sexually intimate (aOR = 1.3, 95% CI 1.030–1.630) had higher odds of having underweight children. Further, findings indicate that the random intercepts is near zero (0) suggesting no cross-section unit to unit variation. Conclusion Recognizing the impact and influence of family dynamics in driving underweight is crucial in the holistic development of interventions beyond conventional community and health interventions.